2019
DOI: 10.1186/s12906-019-2589-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, synthesis and antibacterial evaluation of phenolic compounds from Cylicodiscus gabunensis

Abstract: Background Cylicodiscus gabunensis Harms (Family Leguminosae ) (CG) is an African medicinal plant used as a treatment of various ailments including malaria, liver diseases, and gastrointestinal disturbances. Its extracts showed potent in vitro antibacterial activity. However, the antibacterial components are unknown. Methods In this study, the stem bark of the CG plant was extracted and its antibacterial property against a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Indeed, they are usually reported as being essential for the biological effects, for example, the antiplasmodial activity of caffeic acid derivatives or the antibacterial effect of gallate derivatives. [27,32] Therefore, easily reversible protective groups were inserted through an acetylation reaction (24-27, Figure 3) while phenol methylation was performed, resulting in a less-labile protective group (31-34, Figure 3). [32,34] Moreover, to show if these O-alkyl substituents were sufficient to increase the antiplasmodial activity of our hit compounds, we also prepared their corresponding acid derivatives (28-30 and 35-37, Figure 3).…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, they are usually reported as being essential for the biological effects, for example, the antiplasmodial activity of caffeic acid derivatives or the antibacterial effect of gallate derivatives. [27,32] Therefore, easily reversible protective groups were inserted through an acetylation reaction (24-27, Figure 3) while phenol methylation was performed, resulting in a less-labile protective group (31-34, Figure 3). [32,34] Moreover, to show if these O-alkyl substituents were sufficient to increase the antiplasmodial activity of our hit compounds, we also prepared their corresponding acid derivatives (28-30 and 35-37, Figure 3).…”
Section: Chemistrymentioning
confidence: 99%
“…[32,34] Moreover, to show if these O-alkyl substituents were sufficient to increase the antiplasmodial activity of our hit compounds, we also prepared their corresponding acid derivatives (28-30 and 35-37, Figure 3). Consequently, acetylated prodrugs were obtained after reaction with acetic anhydride (Ac 2 O) and sulfuric acid, following the process described by Gokcen et al, [34] except for 1,2,3-triacetoxybenzene (27), which required the action of Ac 2 O and pyridine. [34,35] In terms of the methoxylated analogs, the reaction of the hydroxybenzoic acids (31)(32)(33)(34) with dimethylsulfate (DMS) was followed by basic saponification by means of LiOH to cleave the methyl ester (35-37, Figure 3).…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…aureus through affecting the initial attachment phase of biofilm development (Wu, Liu, Bai, et al, 2019; Wu, Liu, Zhu, & Shen, 2019). Numerous studies have demonstrated that phenolic compounds possess multi‐target antibacterial mechanisms against pathogens, including damaging cell membrane, interrupting cell wall, binding to bacterial DNA, and inhibiting the synthesis of proteins and nuclear acids (Aldulaimi, Drijfhout, Uche, Horrocks, & Li, 2019; Niu et al, 2019; Wang, Zou, Xie, & Xie, 2014). However, further information at molecular level for elucidation of the antibacterial mechanism of phenolic compounds was not well understood.…”
Section: Introductionmentioning
confidence: 99%